A case of grade V renal trauma with total avulsion of renal artery and vein: Management strategies and outcomes - Ibrahim Boukhannous; Wassim Alaoui Mhammedi; Yacoub Ahmed Okiyeh; Abdelghani Ouraghi; Anouar EL Moudane; Ali Barki (Urology Case Reports, 2023)
Renal trauma is a serious condition that can result in significant morbidity and mortality, particularly in the case of Grade V injuries with complete avulsion of the renal artery and vein. We report a case of a 22-year-old male who sustained a Grade V renal injury in a motor vehicle accident resulting in total avulsion of the renal artery and vein. The patient underwent immediate surgical exploration with successful nephrectomy and ligation of the renal pedicle. This case reports aims to discuss the management strategies for severe renal injuries and the outcomes associated with this approach.